Reproducible Econometric Simulations - Christian Kleiber; Achim Zeileis (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
Reproducibility of economic research has attracted considerable attention in recent years. So far, the discussion has focused on reproducibility of empirical analyses. This paper addresses a further aspect of reproducibility, the reproducibility of computational experiments. We examine the current situation in econometrics and derive a set of guidelines from our findings. To illustrate how computational experiments could be conducted and reported we present an example from time series econometrics that explores the finite-sample power of certain structural change tests.
Keywords: C; 330; computational experiment; reproducibility; simulation; software.; Ökonometrisches Modell; Simulation; Test